PEDAGOGICAL CONDITIONS AND FEATURES OF FORMATION OF PROFESSIONAL COMPETENCE TO FUTURE SPECIALISTS IN PHYSICAL THERAPY, ERGOTHERAPY - Валентина КРУПА; Ірина ЛОБОДА (Bohdan Khmelnytskyi National Academy of the State Border Guard Service of Ukraine, 2021)
The article reveals the content of the defined in the study pedagogical conditions of training physical rehabilitation specialists in higher education institutions. The features and impact of these conditions on the quality of training of specialists as one of the main elements of the fundamental basic components of improving the educational process in an educational institution are briefly presented. Various aspects of training future specialists in physical rehabilitation are presented in the works of national and foreign scientists. The study of the issues of forming the professional competence to physical rehabilitation specialists is one of the topical areas of interdisciplinary research, both in our country and abroad. Methodological and theoretical aspects of the development of personal professional competence have been considered by scientists of different generations. The authors focus on the fact that the reform of higher education and Ukraine's entry into the European educational and scientific space is due to increasing demands on the professionalism of graduates of higher education institutions in a competitive market environment. Orientation on the development of the student as a personality, individuality and active subject of professional activity can be realized only on the humanistic and democratic basis of pedagogical activity in higher education institutions. In the process under study, there is a whole set of contradictions that require a constructive solution. In order to eliminate these contradictions, there was conducted a study and worked out the pedagogical technology to improve the formation of professional competence to physical rehabilitation specialists. The authors made appropriate conclusions about the participation of the teaching staff for improving this process and the features of the psychological readiness of students for their future profession.